1996
DOI: 10.1111/j.1553-2712.1996.tb03430.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Quality Improvement Reduces Length of Stay for Fast‐track Patients in an Emergency Department

Abstract: Objective: To demonstrate how continuous quality improvement (CQI) can identify rational and effective means to reduce length of stay for minor illnesshnjury in an ED.Methods: A CQI team documented the process of fast-track (FT) patient flow and prioritized the causes of deiay. In Phase I, two solutions were implemented. In this Phase I1 of the study, three changes were implemented, including expansion of the FT area, realignment to provide a full-time FT nurse, and a detailed, stricter triage classification. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 15 publications
0
40
0
1
Order By: Relevance
“…However, the causes are interrelated and multifaceted and include increased medical complexity and acuity, increased overall patient volume, a lack of inpatient beds, shortages of physicians, nurses, and staff, delays in laboratory or radiology results, and limited space within the ED [20][21][22][23]. Besides the implementation of standing orders, numerous studies demonstrate that other changes in throughput, such as modifications to capacity, triage, laboratory testing, staffing, and registration, improve ED LOS [7,8,[24][25][26][27]. Along the same lines, the placement of a physician or midlevel provider at triage is an alternative strategy to triage standing orders [5,28].…”
Section: Discussionmentioning
confidence: 99%
“…However, the causes are interrelated and multifaceted and include increased medical complexity and acuity, increased overall patient volume, a lack of inpatient beds, shortages of physicians, nurses, and staff, delays in laboratory or radiology results, and limited space within the ED [20][21][22][23]. Besides the implementation of standing orders, numerous studies demonstrate that other changes in throughput, such as modifications to capacity, triage, laboratory testing, staffing, and registration, improve ED LOS [7,8,[24][25][26][27]. Along the same lines, the placement of a physician or midlevel provider at triage is an alternative strategy to triage standing orders [5,28].…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] Such a process focuses on CTAS 4 and 5 patients, who otherwise are a very low priority and sometimes even overlooked. The LWBS proportion is primarily a measure of efficiency in the care of CTAS 4 and 5 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible concern is that patient satisfaction may have worsened as a result of HUGO. It has been shown that the LWBS proportion is an indicator of patient satisfaction [16][17][18][19] ; an increasing proportion of LWBS may be an early signal that a department may need to urgently address patient dissatisfaction before institutional reputation is permanently harmed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Clawson and colleagues recently reported that, by providing emergency medical dispatchers with regular and objective performance feedback for a two-month period, their mean overall compliance score with dispatch protocols increased from 76% to 96%. 4 Other relevant ED CQI projects have been published, describing improvements in doorto-drug thrombolytic intervals, 5,6 EMS documentation, 7 patient length of stay and walkouts, 8,9 stat laboratory services, 10 radiograph callbacks, 11 and ED triage. 12 Our approach was to incorporate basic and time-proven CQI methodology into our initiative.…”
Section: Discussionmentioning
confidence: 99%